Traditional Tibetan medicine: therapeutic potential in rheumatoid arthritis - Yu, Liqiong; Li, Shiling; Pu, Lili; Yang, Chunhong; Shi, Qian; Zhao, Qi; Meniga, Shengbu; Liu, Yue; Zhang, Yi; Lai, Xianrong (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis (RA) is a severe inflammatory autoimmune disease characterized by the failed spontaneous resolution of inflammation. The induction of immune regulation and resolution of inflammatory pathways are effective in alleviating inflammation in RA. As the oldest medical system in the world, traditional Tibetan medicine (TTM) has a long history of preventing and treating RA. This review provides a comprehensive overview of medicinal plants with anti-RA activity in the TTM system, using classic books of Tibetan medicine, modern research literature, and drug standards. A total of 27 species have been found to be effective in treating RA, including Tinospora sinensis (Lour.) Merr., Terminalia chehula Retz., P. hookeri (C. B. Clarke) Hock.), and Aconitum pendulum Busch. Alkaloids, flavonoids, polyphenols, and terpenoids have turned out to be the major bioactive components for RA treatment. The inhibition of pro-inflammatory cytokine expression by mediating the NF-κB, MAPK, and JAK/STAT pathways is the core mechanism in RA treatment. In conclusion, this review provides key information and research perspectives for further research on the anti-RA effects of TTM.